Comparative Typology of Science and Religion Integration of Syed Muhammad Naquib Al-Attas and Amin Abdullah and its Implications for Islamic Education - Riwanda, Agus (Universitas Nahdlatul Ulama Surabaya, 2023)
This The main aim of this study is to analyze and clarify the implementation of the integration of science and religion, as suggested by Islamic scholars from Southeast Asia, in educational settings, particularly in State Islamic Universities and high schools in Indonesia. This research uses library research methodology to investigate the Comparative Typology of Integration of Science and Religion proposed by Syed Muhammad Naquib Al-Attas and Amin Abdullah and its consequences for Islamic education. Al-Attas emphasized the importance of balancing spiritual and practical knowledge, recognizing both personal religious experience and objective religious elements. It supports the advancement of scientific knowledge through observation and experimentation and encourages the development of creative thinking and imagination in acquiring knowledge. On the other hand, Amin Abdullah advocates a relationship between science and religion that allows some information to flow, emphasizing the importance of mutual understanding and the integration of imaginative thinking into Islamic education to make it more relevant to today's times. To improve Islamic education, it is essential to achieve a balance between spiritual and practical knowledge, promote understanding of the simultaneous existence of subjective and objective aspects in religion, encourage scientific enlightenment and critical thinking, stimulate creativity and innovation in learning, facilitate viable connections between sciences and religion, recognizing the duality of objective and subjective components in religious studies, and integrating creative thinking to make religious education relevant and interesting in contemporary cultural contexts. These approaches can improve the quality of Islamic education and equip students to face the complexities of faith, science, and culture in the modern world.